A micro-epidemiological analysis of febrile malaria in Coastal Kenya showing hotspots within hotspots - Bejon, P; Williams, T; Nyundo, C; Hay, S; Benz, D; Gething, P; Otiende, M; Peshu, J; Bashraheil, M; Greenhouse, B; Bousema, T; Bauni, E; et al. (eLife Sciences Publications, 2014)
Malaria transmission is spatially heterogeneous. This reduces the efficacy of control strategies, but focusing control strategies on clusters or ‘hotspots’ of transmission may be highly effective. Among 1500 homesteads in coastal Kenya we calculated (a) the fraction of febrile children with positive malaria smears per homestead, and (b) the mean age of children with malaria per homestead. These two measures were inversely correlated, indicating that children in homesteads at higher transmission acquire immunity more rapidly. This inverse correlation increased gradually with increasing spatial scale of analysis, and hotspots of febrile malaria were identified at every scale. We found hotspots within hotspots, down to the level of an individual homestead. Febrile malaria hotspots were temporally unstable, but 4 km radius hotspots could be targeted for 1 month following 1 month periods of surveillance.